Electrocatalytic and voltammetric determination of sulfhydryl compounds through iron nitroprusside modified graphite paste electrode - Do Carmo, Devaney R. [UNESP]; Da Silva, Ricardo M. [UNESP]; Stradiotto, Nelson Ramos [UNESP] (FapUNIFESP (SciELO), 2003)
Iron nitroprusside Fe(II)NP was incorporated into a carbon paste electrode and the electrochemical studies were performed with cyclic voltammetry. The cyclic voltammogram of Fe(II)NP exhibits two redox couple with formal potential (E0')1 = 0.24 e (E0')2 = 0.85 V vs SCE attributed to Fe(II)/Fe(II) and Fe (II)(CN)5NO/Fe(III)(CN)5NO, respectively. The redox couple with (E0')2 = 0.85 V presents an electrocatalytic response for sulfhydryl compounds. The electrocatalytic oxidation of sulfhydryl compounds by the mediator has been used for the determination of L-cysteine and N-acetylcysteine. The modified graphite paste electrode gives a linear range from 9.2 x 10-4-2.0 x 10-2;; 9.6 x 10-4-1.4 x 10-2mol L-1 for the determination of L-cysteine and N-acetylcysteine, respectively, with detection limit of 1.9 x 10-4 mol L-1;; 1.5 x 10 -4 mol L-1 and relative standard desviations ± 5% and 1.5 x 10-3 mol L-1 ± 4% (n=3). The amperometric sensitivities are 0.024 and 0.027 μA/μmol L-1 for L-cysteine and N-acetylcysteine, respectively. The application of this electrode was tested and a commercial pharmaceutical product (Fluimucil) has been determined.
Keywords: Graphite paste electrode; Iron nitroprusside; L-cysteine; N-acetylcysteine; Sulfhydryl compounds; acetylcysteine; carbon; cysteine; graphite; iron; nitroprusside sodium; thiol derivative; amperometry; catalysis; commercial phenomena; conference paper; cyclic potentiometry; electrochemical analysis; electrochemistry; electrode; oxidation reduction reaction; paste; potentiometry